2018
DOI: 10.14419/ijet.v7i4.15.21447
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Selected Macroeconomic Variables on Carbon Dioxide (Co2) Emission in Malaysia

Abstract: This study tries to investigate the relationship between gross domestic product, electricity product, net trade, electricity consumption and oil price on carbon dioxide (Co2) emission in Malaysia. Thus, it uses the Ordinary Least Square (OLS) method in structuring the model estimation. By utilizing yearly time series data from 1980 to 2017, this study focuses on economics and statistical criteria analyses. According to sign analysis, the results suggest that, gross domestic product, electricity product, net tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Specifically, this study also revealed the significant role played by total energy consumption in Malaysia and Singapore. The outcome is supported by most of the past studies including Bekhet (2013), Kasman et al (2015), Rambeli et al (2018) and Rambeli et al (2019). Most of these findings agreed that energy consumption impacted on CO2 emissions in both long-and short-run.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Specifically, this study also revealed the significant role played by total energy consumption in Malaysia and Singapore. The outcome is supported by most of the past studies including Bekhet (2013), Kasman et al (2015), Rambeli et al (2018) and Rambeli et al (2019). Most of these findings agreed that energy consumption impacted on CO2 emissions in both long-and short-run.…”
Section: Discussionsupporting
confidence: 69%
“…The success of a country in achieving sustainable economic development status is often associated with its ability to control environmental pollution as well as the ability to maintain environment sustainability. Consistent with this, some recent empirical studies have emphasized that the fall in carbon dioxide (CO2) emissions is a sign of environmental quality enhancement for the country (Rambeli et al 2018;Harris et al 2017;Halicioglu 2009;Green & Stern 2017;Mckibbin et al 2017;Adamu et al 2021). With such coverage in the literature it therefore cannot be denied that the relationship has been given attention by policymakers and researchers, ever since the achievement of sustained economic growth is gradually becoming a major global concern.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Various studies have focused on environmental issues and restraining severe global warming, which may lead to a serious matter. In Malaysia, National Policy on climate change has been enforced to provide a framework that could guide all government agencies, industries, communities, and other stakeholders to face challenges in climate change scenarios (Rambeli-Ramli et al, 2018). The policy has been imposed to ensure climate-resilient development to fulfill national aspirations for the sustainability of its environment.…”
Section: Introductionmentioning
confidence: 99%
“…Malaysia also plans to reduce greenhouse gas emissions while installing the Green Technology Master Plan 2017-2030(Ali et al, 2018Sulaiman and Shabri, 2021)). In a careful calculation, carbon dioxide is the primary component of greenhouse gasses and the primary cause of climate variation and global warming (Rambeli-Ramli et al, 2018). In layperson's terms, the amount of carbon dioxide in the atmosphere has increased significantly (Yuaningsih et al, 2021).…”
Section: Introductionmentioning
confidence: 99%